Nurse’s actions in the interface with expanded services of Family Health and Primary Care Center - Vendruscolo, Carine; Silva, Kátia Jamile da; Durand, Michelle Kuntz; Metelski, Fernanda Karla; Silva Filho, Cláudio Claudino da (Revista da Escola de Enfermagem da USP, 2020)
Objective To understand the actions of nurses from the perspective of the interface of performing with the Expanded Services of Family Health and Primary Care Center. Method Qualitative participatory research based on the Freirean Itinerary, from the following steps: thematic research; encoding and decoding; and critical unveiling. The information was obtained through four Culture Circles, with nurses from Family Health teams, between April and June 2018. Results A total of nine nurses participated in the study. Among the generative topics emerged, there is the “relationship between generalist teams and the health center: nurses as a reference and interprofessional bond”. Nurses perceive themselves in this way because of generalist and managerial training. Shared activities as groups are among the practices developed collectively and that strengthen interprofessional work. Conclusion By provoking reflections on autonomy and the work process in collaborative performance with the Centers, the study expanded the perception about the actions developed by nurses in the interaction with the multiprofessional team. It is suggested to carry out other studies on interprofessionality in the relationship between nursing and the extended services through the perspective of the Center professionals.